Is Mutual Fund Flow Related with Fund Performance? An Empirical Study of Regular Plan Mutual Funds in India - Singh, Shveta; Dipika (Indian Journal of Research in Capital Markets, 2021)
This paper examined the fund flow and fund performance relationship using sample data of 144 Indian open-ended equity and balanced regular mutual funds, consisting of eight different fund categories from April 2014 to March 2018. We observed a significant positive association between fund flow and fund recent past performance through Sirri and Tufano (1998) fractional flow model, piecewise regression, and Fama-MacBeth’s (1973) regression. The results reported that retail investors were sensitive towards the fund’s recent past performance and it indicated the relative sophistication in the Indian mutual fund industry. The findings, as supported by the negative and significant coefficients of all panels, suggested that retail investors preferred investing in less risky funds. The study provided insights into the investment behavior, too, in terms of fund flow and their relationship with funds’ recent performance, risk, expense ratio, fund category flow, fund’s age, asset management company’s age, and the experience of the fund manager. This is a pioneering work that estimated the regular plan fund flow-performance relationship post regulatory reforms, such as the introduction of direct plans, the extra commission allowed to beyond the top 15 cities (B15 cities) distributors, introduced by the Securities and Exchange Board of India.